PROBABILITY OF DEFAULT, INTEREST MARGIN, AND BANK EFFICIENCY: EMPIRICAL TEST OF MERTON MODEL IN INDONESIAN BANKING - Wibowo, Buddi (Jurnal Aplikasi Manajemen, 2017)
Measurement of bank failure risk is still a challenging research problem. This study is aimed to measure the Indonesia banks probability of bankruptcywith Model Merton which has the better predictive power and is based on a far stronger financial theoretical frameworkcompared to the popular bankruptcy prediction model which is categorized by Sundaresan (2013) as a theoretical model such as Altman Z-score model and Ohlson 0 score more popular. The study also examine the relationship of bank efficiency and market power with its probability of default. The test results demonstrate that bank efficiency significantly affects the dynamics of bank's default risk.